Whole genome sequence analysis of unidentified genetically modified papaya for development of a specific detection method. (15th August 2016) - Nakamura, Kosuke; Kondo, Kazunari; Akiyama, Hiroshi; Ishigaki, Takumi; Noguchi, Akio; Katsumata, Hiroshi; Takasaki, Kazuto; Futo, Satoshi; Sakata, Kozue; Fukuda, Nozomi; Mano, Junichi; Kitta, Kazumi; et al.
Highlights: Unknown genetically modified (GM) papaya ( Carica papaya Linnaeus) was identified by whole genome sequence analysis. Contigs having transgenic construct- and event-specific DNA sequences in GM papaya were found. Searches of GM papaya whole genome sequence data were possible using common transgenic sequences (>17 bp). A method for real-time PCR detection of GM papaya from whole genome sequence data was developed. Abstract: Identification of transgenic sequences in an unknown genetically modified (GM) papaya ( Carica papaya L.) by whole genome sequence analysis was demonstrated. Whole genome sequence data were generated for a GM-positive fresh papaya fruit commodity detected in monitoring using real-time polymerase chain reaction (PCR). The sequences obtained were mapped against an open database for papaya genome sequence. Transgenic construct- and event-specific sequences were identified as a GM papaya developed to resist infection from a Papaya ringspot virus . Based on the transgenic sequences, a specific real-time PCR detection method for GM papaya applicable to various food commodities was developed. Whole genome sequence analysis enabled identifying unknown transgenic construct- and event-specific sequences in GM papaya and development of a reliable method for detecting them in papaya food commodities.